2018
DOI: 10.1016/j.etap.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to a glyphosate-containing pesticide leads to mitochondrial dysfunction and increased reactive oxygen species production in Caenorhabditis elegans

Abstract: Glyphosate-containing herbicides are among the most widely-used in the world. Although glyphosate itself is relatively non-toxic, growing evidence suggests that commercial herbicide formulations may lead to increased oxidative stress and mitochondrial inhibition. In order to assess these mechanisms in vivo, we chronically (24h) exposed Caenorhabditis elegans to various concentrations of the glyphosate-containing herbicide TouchDown (TD). Following TD exposure, we evaluated the function of specific mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…In particular, they found that the pesticide destroyed the bacteria of the gastrointestinal tract that acted as guarantors of the natural balance of the intestine of the animals. This is also shown in studies [20,21,53], which consider cattle infections and show their dramatic increase over the past decade. The cause is due to the fact that the debilitated gastrointestinal tract in animals favors the onset of infectious diseases.…”
Section: Scientific Debatesupporting
confidence: 52%
See 3 more Smart Citations
“…In particular, they found that the pesticide destroyed the bacteria of the gastrointestinal tract that acted as guarantors of the natural balance of the intestine of the animals. This is also shown in studies [20,21,53], which consider cattle infections and show their dramatic increase over the past decade. The cause is due to the fact that the debilitated gastrointestinal tract in animals favors the onset of infectious diseases.…”
Section: Scientific Debatesupporting
confidence: 52%
“…In addition, numerous studies [15,20,27] have been performed on mice and rats by administering high doses of glyphosate. The results show that the substance causes growth delays, kidney damage, liver enlargement and inflammation, and gastric disease [15,20,21]. Also, for aquatic plant organisms, glyphosate is considered toxic and acts by altering the vital functions related to photosynthesis, respiration, and the synthesis of essential aromatic amino acids.…”
Section: Human and Animals Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…pH) environmental conditions, glyphosate’s half-life can last from days to months (e.g. 7–70 days in the water; Giesy et al, 2000), leading to possible chronic exposures for organisms living in certain environments (Feng et al, 1990; Borggaard and Gimsing, 2008; Bailey et al, 2018). GBH formulations are generally more toxic than glyphosate by itself, mainly due to the presence of surfactants (e.g.…”
Section: Introductionmentioning
confidence: 99%